Changes in GEDI-based measures of forest structure after large California wildfires relative to pre-fire conditions - Matthew L. Clark; Christopher R. Hakkenberg; Tim Bailey; Patrick Burns; Scott J. Goetz (Remote Sensing of Environment, 2025)

Toxicological assessment of E-cigarette flavored E-liquids aerosols using Calu-3 cells: A 3D lung model approach - Felix Effah; John Adragna; David Luglio; Alexis Bailey; Tim Marczylo; Terry Gordon (Toxicology, 2023)

In Vitro high-throughput toxicological assessment of E-cigarette flavors on human bronchial epithelial cells and the potential involvement of TRPA1 in cinnamon flavor-induced toxicity - Felix Effah; Atallah Elzein; Benjamin Taiwo; Deborah Baines; Alexis Bailey; Tim Marczylo (Toxicology, 2023)

Cerebrovascular function and its association with systemic artery function and stiffness in older adults with and without mild cognitive impairment - Tom G. Bailey; Timo Klein; Annelise L. Meneses; Kayla B. Stefanidis; Stefanie Ruediger; Daniel J. Green; Tim Stuckenschneider; Stefan Schneider; Christopher D. Askew (European Journal of Applied Physiology, 2022)
Purpose Our aim was to compare cerebrovascular and systemic vascular function between older adults with and without mild cognitive impairment (MCI), and to determine which measures of vascular function best predict the presence of MCI. Methods In 41 adults with MCI and 33 adults without MCI (control) we compared middle cerebral artery velocity (MCAv) and cerebrovascular pulsatility index (PI) at rest, cerebrovascular reactivity to CO 2 , and responsiveness to changes in blood pressure (%∆MCAv/%∆MAP). Systemic vascular function was assessed by flow-mediated dilation (FMD) and stiffness by pulse wave velocity (PWV). Results Cerebrovascular PI was higher in MCI compared with control (mean ± SD: 1.17 ± 0.27 vs. 1.04 ± 0.21), and MCI exhibited a lower %∆MCAv/%∆MAP (1.26 ± 0.44 vs. 1.50 ± 0.55%). Absolute ( p = 0.76) and relative cerebrovascular reactivity to CO 2 ( p = 0.34) was similar between MCI and control. When age was included as a covariate the significant difference in cerebral PI between groups was lost. PWV was higher (13.2 ± 2.2 vs. 11.3 ± 2.5 m s −1 ) and FMD% (4.41 ± 1.70 vs. 5.43 ± 2.15%) was lower in MCI compared with control. FMD% was positively associated with PI across the cohort. Logistic regression analysis indicated that FMD and PWV significantly discriminated between MCI and controls, independent of age, whereas the inclusion of cerebrovascular measures did not improve the predictive accuracy of the model. Conclusion These findings raise the possibility that early changes in systemic vascular stiffness and endothelial function may contribute to altered cerebrovascular haemodynamics and impaired cognitive function, and present potential targets for prevention and treatment strategies in people with MCI.

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Mesenchymal Stromal Cell‐derived Extracellular Vesicles in Preclinical Animal Models of Tumor Growth: Systematic Review and Meta‐analysis - Adrian J.M. Bailey; Alvin Tieu; Manika Gupta; Mitchell Slobodian; Risa Shorr; Tim Ramsay; Rosendo A. Rodriguez; Dean A. Fergusson; Manoj M. Lalu; David S. Allan (Stem Cell Reviews and Reports, 2022)

SoilTemp: A global database of near‐surface temperature - Jonas J. Lembrechts; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Martin Kopecký; Jonathan Lenoir; Miska Luoto; Ilya M. D. Maclean; Olivier Roupsard; Eduardo Fuentes‐Lillo; Rafael A. García; Loïc Pellissier; et al. (Global Change Biology, 2020)
Current analyses and predictions of spatially explicit patterns and processes in ecology most often rely on climate data interpolated from standardized weather stations. This interpolated climate data represents long‐term average thermal conditions at coarse spatial resolutions only. Hence, many climate‐forcing factors that operate at fine spatiotemporal resolutions are overlooked. This is particularly important in relation to effects of observation height (e.g. vegetation, snow and soil characteristics) and in habitats varying in their exposure to radiation, moisture and wind (e.g. topography, radiative forcing or cold‐air pooling). Since organisms living close to the ground relate more strongly to these microclimatic conditions than to free‐air temperatures, microclimatic ground and near‐surface data are needed to provide realistic forecasts of the fate of such organisms under anthropogenic climate change, as well as of the functioning of the ecosystems they live in. To fill this critical gap, we highlight a call for temperature time series submissions to SoilTemp, a geospatial database initiative compiling soil and near‐surface temperature data from all over the world. Currently, this database contains time series from 7,538 temperature sensors from 51 countries across all key biomes. The database will pave the way toward an improved global understanding of microclimate and bridge the gap between the available climate data and the climate at fine spatiotemporal resolutions relevant to most organisms and ecosystem processes.

Characterization of Highper, an ENU-induced mouse mutant with abnormal psychostimulant and stress responses - Amy F. Eisener-Dorman; Janice S. Bailey; Laura Grabowski-Boase; Salvador Huitron-Resendiz; Amanda J. Roberts; Tim Wiltshire; Lisa M. Tarantino (Psychopharmacology, 2013)

Pervasive effects of dispersal limitation on within‐ and among‐community species richness in agricultural landscapes - Frederik Hendrickx; Jean‐Pierre Maelfait; Konjev Desender; Stephanie Aviron; Debra Bailey; Tim Diekotter; Luc Lens; Jaan Liira; Oliver Schweiger; Marjan Speelmans; Viki Vandomme; Rob Bugter (Global Ecology and Biogeography, 2009)
Aim To determine whether the effect of habitat fragmentation and habitat heterogeneity on species richness at different spatial scales depends on the dispersal ability of the species assemblages and if this results in nested species assemblages. Location Agricultural landscapes distributed over seven temperate Europe countries covering a range from France to Estonia. Methods We sampled 16 local communities in each of 24 agricultural landscapes (16 km 2 ) that differ in the amount and heterogeneity of semi‐natural habitat patches. Carabid beetles were used as model organisms as dispersal ability can easily be assessed on morphological traits. The proximity and heterogeneity of semi‐natural patches within the landscape were related to average local (alpha), between local (beta) and landscape (gamma) species richness and compared among four guilds that differ in dispersal ability. Results For species assemblages with low dispersal ability, local diversity increased as the proximity of semi‐natural habitat increased, while mobile species showed an opposite trend. Beta diversity decreased equally for all dispersal classes in relation to proximity, suggesting a homogenizing effect of increased patch isolation. In contrast, habitat diversity of the semi‐natural patches affected beta diversity positively only for less mobile species, probably due to the low dispersal ability of specialist species. Species with low mobility that persisted in highly fragmented landscapes were consistently present in less fragmented ones, resulting in nested assemblages for this mobility class only. Main conclusions The incorporation of dispersal ability reveals that only local species assemblages with low dispersal ability show a decrease of richness as a result of fragmentation. This local species loss is compensated at least in part by an increase in species with high dispersal ability, which obscures the effect of fragmentation when investigated across dispersal groups. Conversely, fragmentation homogenizes the landscape fauna for all dispersal groups, which indicates the invasion of non‐crop habitats by similar good dispersers across the whole landscape. Given that recolonization of low dispersers is unlikely, depletion of these species in modern agricultural landscapes appears temporally pervasive.

Prediction uncertainty of environmental change effects on temperate European biodiversity - Carsten F. Dormann; Oliver Schweiger; P. Arens; I. Augenstein; St. Aviron; Debra Bailey; J. Baudry; R. Billeter; R. Bugter; R. Bukácek; F. Burel; M. Cerny; et al. (Ecology Letters, 2008)
Observed patterns of species richness at landscape scale (gamma diversity) cannot always be attributed to a specific set of explanatory variables, but rather different alternative explanatory statistical models of similar quality may exist. Therefore predictions of the effects of environmental change (such as in climate or land cover) on biodiversity may differ considerably, depending on the chosen set of explanatory variables. Here we use multimodel prediction to evaluate effects of climate, land‐use intensity and landscape structure on species richness in each of seven groups of organisms (plants, birds, spiders, wild bees, ground beetles, true bugs and hoverflies) in temperate Europe. We contrast this approach with traditional best‐model predictions, which we show, using cross‐validation, to have inferior prediction accuracy. Multimodel inference changed the importance of some environmental variables in comparison with the best model, and accordingly gave deviating predictions for environmental change effects. Overall, prediction uncertainty for the multimodel approach was only slightly higher than that of the best model, and absolute changes in predicted species richness were also comparable. Richness predictions varied generally more for the impact of climate change than for land‐use change at the coarse scale of our study. Overall, our study indicates that the uncertainty introduced to environmental change predictions through uncertainty in model selection both qualitatively and quantitatively affects species richness projections.

Bacterial diversity is determined by volume in membrane bioreactors - Christopher J. Van Der Gast; Bruce Jefferson; Elizabeth Reid; Tim Robinson; Mark J. Bailey; Simon J. Judd; Ian P. Thompson (Environmental Microbiology, 2006)
Summary It has been proposed that established models and theories developed in classical ecology could be employed to greatly improve the optimization of wastewater treatment plants (WWTP) by placing the microbiological component onto a model‐predictive basis. In particular, this could be achieved by better understanding bacterial community assembly and development. The species–area relationship is one of the oldest biological laws and has been used to describe spatial diversity patterns in contiguous habitats and on islands. In the current study, bacterial communities in seven membrane bioreactors (MBR), of increasing size, located across the UK were sampled. A significant linear relationship between bacterial taxa richness and reactor size was observed and was similar to classical species–area relationships of larger organisms colonizing oceanic islands. Rank‐abundance plots revealed a gradient of greater evenness in community structure as MBR volume increased. Application of the Raup and Crick probability‐based similarity index indicated a strong role for dispersal in MBR colonization and community structure. Our findings demonstrate that the MBR sampled behaved like islands with respect to bacterial colonization in accordance with the theory of island biogeography. In addition this study provides further evidence that biodiversity at the bacterial level is more similar to that of animals and plants than previously postulated.